| **Giver** | **Post** | **Date** |

| anirudh1993 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 27-Mar-2021 |

| jannik31 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 23-Mar-2021 |

| MBaliarsingh | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 12-Mar-2021 |

| RiotingEskimo | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 31-Jan-2021 |

| RanjithJN | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 26-Jan-2021 |

| Mannyyaa | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 10-Jan-2021 |

| dverma92 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 24-Dec-2020 |

| 1610ayush | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 13-Dec-2020 |

| suyashjain96 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 11-Dec-2020 |

| eyeneed8hunnit | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 11-Dec-2020 |

| Draky | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 17-Nov-2020 |

| jahid12 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 25-Oct-2020 |

| hankim0624 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 06-Oct-2020 |

| Mariaaa | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 15-Sep-2020 |

| yan315 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 30-Aug-2020 |

| Krishna15 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 24-Aug-2020 |

| sayeed mozomder | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 12-Aug-2020 |

| BorisDa | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 10-Aug-2020 |

| lukey123 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 26-Jun-2020 |

| UnlikelyRooster | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 26-Jun-2020 |

| chimpscampi91 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 17-Jun-2020 |

| varunprana | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 27-May-2020 |

| Farjin | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 05-May-2020 |

| thenikhilseth | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 25-Apr-2020 |

| montanhaf100 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 09-Apr-2020 |

| ppolyako | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 20-Mar-2020 |

| Nadja1234 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 08-Mar-2020 |

| Rebaz | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 28-Feb-2020 |

| Gairavivek | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 15-Jan-2020 |

| munter | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 04-Jan-2020 |